Can order entry systems improve oncology practice? The TrACER Experience. Issue 28 (1st October 2022) - Ramsey, Scott David; Bansal, Aasthaa; Barlow, William E.; Arnold, Kathryn B.; Bell-Brown, Ari; Watabayashi, Kate; Kreizenbeck, Karma L.; Lyman, Gary H.; Sullivan, Sean D; Hershman, Dawn L.
Abstract : 339 Background: Primary prophylactic colony stimulating factors (PP-CSF) are prescribed to patients undergoing chemotherapy to reduce the risk of febrile neutropenia (FN). Prior research suggested poor adherence to PP-CSF prescribing relative to national guidelines. Accordingly, the objective of the TrACER study was to examine whether a guideline-based standing order entry (SOE) system for PP-CSF improves use and reduces FN. TrACER also included a substudy to evaluate the effectiveness of PP-CSF for patients receiving intermediate risk chemotherapy, where evidence of benefit is weaker. Methods: We conducted a patient-informed, cluster randomized trial among 32 oncology clinics from the NCI Community Oncology Research Program. Patients age ≥18 with breast, colorectal or non-small cell lung cancer initiating cancer therapy were enrolled. Clinics were randomized 3:1 to the implementation of a guideline-based PP-CSF SOE or usual care. Automated orders for PP-CSF were added for high-risk regimens and an alert not to use PP-CSF was included for low-risk regimens. Risk was based on National Comprehensive Cancer Network guidelines. A secondary 1:1 randomization for intermediate risk-regimens assigned 16 intervention sites to either SOE to prescribe or an alert to not prescribe PP-CSF. Results: 2, 946 patients were enrolled (2287 intervention, 659 usual care). PP-CSF use among high-risk patients was high and not significantly different between arms (89.2% SOE; 95.8% usual care). FN rates for the SOE and usual care arms were 6.1% and 4.2% and not significantly different. The FN rate among high-risk patients not receiving PP-CSF was 14.9%. Among the 585 patients receiving low-risk regimens, PP-CSF use was low and not different between arms (6.3% SOE, 5.5% usual care). FN rates did not differ between the SOE system (1.5%) and usual care (0.8%). In contrast, for the intermediate risk substudy, rates of PP-CSF use were substantially higher among sites randomized to SOE (37.1% vs 9.9%, OR = 5.91(95% CI 1.77-19.70; p = 0.0038), and rates of FN were low and identical between arms (3.7% vs 3.7%). Similarly, FN rates did not differ between intermediate-risk patients that did or did not receive PP-CSF, irrespective of assignment. Conclusions: Implementation of a guideline-informed SOE system did not impact PP-CSF use or FN rates in high- and low-risk patients, where evidence supporting PP-CSF is stronger, and had a significant impact on PP-CSF use but not FN rates among intermediate risk patients, where evidence of benefit is weak. Overall, adherence to PP-CSF for low- and high-risk chemotherapy was much better than predicted based on evidence available at trial design. SOE interventions may be more useful in situations where more uncertainty of benefit exists. The pragmatic trial design provides high-quality evidence that had previously been lacking on the use and performance of PP-CSF in real world settings across the spectrum of FN risk. Clinical trial information: NCT02728596.